2008
DOI: 10.1111/j.1471-6712.2007.00509.x
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes towards people with mental illness: a cross‐sectional study among nursing staff in psychiatric and somatic care

Abstract: Stigma and discrimination have been identified as important obstacles to the integration of people with mental illness in society. In efforts to reduce stigma and discrimination, health professionals play an important role as they have frequent contact with and responsibility for treatment and rehabilitation of consumers. The aim of the present study was to investigate attitudes towards mental illness and people with mental illness among nursing staff working in psychiatric or somatic care. The sample consiste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
138
4
10

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(158 citation statements)
references
References 16 publications
6
138
4
10
Order By: Relevance
“…Although participants seemed to agree, in principle, that mental health care facilities can, and should be, placed in communities, they also expressed a desire for social distance from persons with mental disorders. These findings are in line with international studies (Bjorkman et al, 2008;Arvaniti et al, 2009;Kopera, Suszek, Bonar, Myszka, Gmaj, Wojnar, 2015) and local studies conducted in Africa (Ukpong & Abasiubong, 2010;Barke et al, 2011 andJames, Omoaregba &Okogbenin, 2012).…”
Section: Discussionsupporting
confidence: 91%
“…Although participants seemed to agree, in principle, that mental health care facilities can, and should be, placed in communities, they also expressed a desire for social distance from persons with mental disorders. These findings are in line with international studies (Bjorkman et al, 2008;Arvaniti et al, 2009;Kopera, Suszek, Bonar, Myszka, Gmaj, Wojnar, 2015) and local studies conducted in Africa (Ukpong & Abasiubong, 2010;Barke et al, 2011 andJames, Omoaregba &Okogbenin, 2012).…”
Section: Discussionsupporting
confidence: 91%
“…[8][9][10] This could be related to the increased contact they have with people with mental disorders and, of course, to the fact that helping people with mental health problems is their main work. Professionals in non-mental health settings regarded people with mental health disorders as significantly more dangerous and unpredictable than did the mental health group.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that doctors and nursing staff working in psychiatry had more positive attitudes towards people with mental disorders than those working in somatic medicine. [8][9][10] In this study, we also looked specifically at attitudes towards eating disorders, as previous research has shown stigmatising attitudes from healthcare professionals, which may restrict opportunities for effective treatment. 11 We also investigated the level of empathy in professionals working in mental health and non-mental health settings, to determine whether there was any difference in emotional empathy between the groups.…”
mentioning
confidence: 99%
“…3 Despite the high number of people with mental health conditions, mental health has a low priority in South Africa and people with mental health disorders do not receive the care they require in PHC clinics. 4 Despite the important role PHC nurses play in the provision of health to the general population, their attitudes towards people with mental illness are often negative, [5][6][7] and provision and identification of mental health problems by PHC nurses has been shown to be poor because their knowledge to deal with mental health conditions is inadequate. 8,9 Many nurses lack knowledge and skills to identify and manage mental health conditions.…”
Section: Introductionmentioning
confidence: 99%